CONSIDERING THE BILINGUAL BOOKS’ QUALITY IN INDONESIA: HOW DOES IT AFFECT ON CHILDREN’S FOREIGN LANGUAGE LEARNING (International Conference on Social and Islamic Studies, 2021)
There are many bilingual books spread in various bookstores in Indonesia. Bilingual booksare not only used in schools but also used by parents to introduce foreign languages to children from an early age, in this case English. The basic question that arises is, with the wide distribution of the bilingual book, how is the quality standard or quality of the book? In the preliminary research conducted by the author, there were several findings that bilingual books have an English translation version that is not in accordance with the translation rules. This research aimed to describe in more detail these findings. This research was descriptive research with document analysis. The data source of this research was bilingual book. The results of this research indicated that there were inappropriate translations, which included, 1) errors in word selection (diction) 2) translations with Indonesian grammar so that they do not meet English rules 3) inconsistent in word use.These results provided recommendations on the importance of maintaining the quality orquality of bilingual books. In addition, the government needs to supervise publishers andprovide assistance, especially in the publication process.